2021
DOI: 10.3390/ijms22115816
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol Kinase alpha in X Linked Lymphoproliferative Disease Type 1

Abstract: Diacylglycerol kinases are intracellular enzymes that control the balance between the secondary messengers diacylglycerol and phosphatidic acid. DGKα and DGKζ are the prominent isoforms that restrain the intensity of T cell receptor signalling by metabolizing PLCγ generated diacylglycerol. Thus, their activity must be tightly controlled to grant cellular homeostasis and refine immune responses. DGKα is specifically inhibited by strong T cell activating signals to allow for full diacylglycerol signalling which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Furthermore, it was shown that ritanserin can synergise with irradiation and with imatinib, a tyrosine kinase inhibitor, to decrease cell proliferation of mesenchymal glioblastoma cells ( Olmez et al, 2018 ). Similarly, the DGKα-specific inhibitor Amb639752 promotes restimulated apoptosis of cells in vitro and in animal models of X-linked lymphoproliferative disease type 1, which have elevated DGKα activity ( Velnati et al, 2021a , b , 2020 ). These studies, along with our own findings, suggest that ritanserin as well as other DGKα inhibitors would be good candidates to be developed clinically as anti-cancer drugs and to be used in combination with trametinib or other EGFR-Ras pathway inhibitors, particularly in Ras-driven cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that ritanserin can synergise with irradiation and with imatinib, a tyrosine kinase inhibitor, to decrease cell proliferation of mesenchymal glioblastoma cells ( Olmez et al, 2018 ). Similarly, the DGKα-specific inhibitor Amb639752 promotes restimulated apoptosis of cells in vitro and in animal models of X-linked lymphoproliferative disease type 1, which have elevated DGKα activity ( Velnati et al, 2021a , b , 2020 ). These studies, along with our own findings, suggest that ritanserin as well as other DGKα inhibitors would be good candidates to be developed clinically as anti-cancer drugs and to be used in combination with trametinib or other EGFR-Ras pathway inhibitors, particularly in Ras-driven cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that Ritanserin can synergize with irradiation and with Imatinib, a tyrosine kinase inhibitor, to decrease cell proliferation of mesenchymal glioblastoma cells (Olmez et al, 2018). Similarly, the DGK α -specific inhibitor, Amb639752, promotes restimulated apoptosis of cells in vitro and in animal models of X-linked lymphoproliferative disease type 1, which have elevated DGK α activity (Velnati et al, 2021a; Velnati et al, 2021b; Velnati et al, 2020). These studies, along with our own findings, suggests that Ritanserin, as well as other DGK α inhibitors, would be good candidates to be developed clinically as anti-cancer drugs and to be used in combination with Trametinib or other EGFR-RAS pathway inhibitors, particularly in Ras-driven cancers.…”
Section: Discussionmentioning
confidence: 99%
“…WASp presence inhibits DGKa enzymatic activity promoted by calcium, putatively impairing the shift to the active conformation for which the recoverin homology domain is required (31). SAP-deficient cells drives defective cytokine induction and RICD, which are rescued by the DGKa inhibition (14,15). Since a similar defect in RICD and IL-2 induction is present in murine WASp deficient cells (22, 33), we evaluated the effect of DGKa inhibition on RICD, TCR signalling potency, and IL-2 production in WASpdeficient human lymphocytes.…”
Section: Wasp Binds and Directly Inhibits Dgkamentioning
confidence: 99%